Photoionization of Rb\(^{2+}\) Ions Using the Screening Constant by Unit Nuclear Charge Formalism (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
We report in this paper Photoionization data of the Rb\({}^{2+}\) ions. Rydberg series of resonances due to \(4p→ nd\) transitions from the \({}^{2}\)P\({}^°_{3/2}\) ground state and the \({}^{2}\)P\({}^°_{1/2}\) metastable state of Rb\({}^{2+}\) converging to the \(4s^24p^4\) \((^1D_2)\) series limit in Rb\({}^{3+}\) are considered.\ Calculations are performed in the framework of the Screening Constant by Unit Nuclear Charge (SCUNC) formalism and accurate data are tabulated up to \(n=40\).\ It is shown that the SCUNC analytical formulas reproduce with an excellent precision, recent ALS measurements of Macaluso et al. [J. Phys. B: At. Mol. Opt. Phys. 50 (2017)]. New data are tabulated for \(n = 25\)-\(40\).
Keywords: Photoionization; Rydberg series; Ground state; Metastable state; SCUNC; ground state; metastable state; SCUNC.